2020
DOI: 10.1101/2020.11.23.20236968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering early-warning signals of SARS-CoV-2 elimination and resurgence from limited data at multiple scales

Abstract: Discriminating between second waves of community transmission, which necessitate broad-spectrum interventions, and multiple stuttering epidemic chains from repeated importations, which require targeted controls, is crucial for outbreak preparedness. However, necessarily scarce data available in the lull between potential epidemic waves cripples standard inference engines, blurring early-warning signals. We propose a novel framework for denoising inter-wave data, revealing how timely policy in New Zealand achie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 34 publications
(130 reference statements)
0
38
0
Order By: Relevance
“…4 In this context, the abrupt increase in the number of COVID-19 hospital admissions in Manaus during January, 2021 (3431 in Jan 1-19, 2021, vs 552 in Dec 1-19, 2020) is unexpected and of concern (figure). [5][6][7][8][9][10] After a large epidemic that peaked in late April, 2020, COVID-19 hospitalisations in Manaus remained stable and fairly low for 7 months from May to November, despite the relaxation of COVID-19 control measures during that period (figure ).…”
Section: Resurgence Of Covid-19 In Manaus Brazil Despite High Seroprevalencementioning
confidence: 99%
See 2 more Smart Citations
“…4 In this context, the abrupt increase in the number of COVID-19 hospital admissions in Manaus during January, 2021 (3431 in Jan 1-19, 2021, vs 552 in Dec 1-19, 2020) is unexpected and of concern (figure). [5][6][7][8][9][10] After a large epidemic that peaked in late April, 2020, COVID-19 hospitalisations in Manaus remained stable and fairly low for 7 months from May to November, despite the relaxation of COVID-19 control measures during that period (figure ).…”
Section: Resurgence Of Covid-19 In Manaus Brazil Despite High Seroprevalencementioning
confidence: 99%
“…R t was calculated using the EpiFilter method. 10 Lines are median R t estimates; shaded areas are the 95% CIs. R t =Effective reproduction number.…”
Section: Resurgence Of Covid-19 In Manaus Brazil Despite High Seroprevalencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Flaxman et al (2020) and Brauner et al (2020) fitted models of disease dynamics to case count and death data in different countries to estimate the effect of specific non-pharmaceutical interventions on the transmission rate of COVID-19. Modelling studies have indicated the importance of timely interventions for achieving local elimination and averting resurgent waves of COVID-19 in locations like New Zealand and the Australian state of Victoria (Parag et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On 8 June, after 17 consecutive days with no new reported cases, New Zealand officially declared elimination of community transmission following WHO guidelines (Baker et al, 2020c). This decision is supported by modelling work estimating the probability of elimination at this time (Binny et al, 2020c; Parag et al, 2021; Wilson et al, 2020). Between 22 May and 11 August, the only new cases detected were in international arrivals who were required to spend 14 days in government-managed isolation or quarantine facilities (Baker et al, 2020c).…”
Section: Introductionmentioning
confidence: 99%